2015
DOI: 10.1111/liv.12763
|View full text |Cite
|
Sign up to set email alerts
|

Pretransplant urinary proteome analysis does not predict development of chronic kidney disease after liver transplantation

Abstract: Urinary peptidome analysis before liver transplantation failed to identify a peptide pattern associated with the development of CKD at 6 months after liver transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Several studies have shown the importance of GFR monitoring during the first year after surgery as it allows the identification of patients at risk for CKD in the long term. However, we were able to demonstrate that very early creatinine elevation between D3 and D5, which did not meet the criteria for AKI as they are not sensitive enough, was correlated with poorer kidney function at 6 months to 1 year [66,131]. Similarly, the need for temporary dialysis has been identified as a source of CKD [51] in the long run.…”
Section: Post-operative Risk Factorsmentioning
confidence: 78%
See 1 more Smart Citation
“…Several studies have shown the importance of GFR monitoring during the first year after surgery as it allows the identification of patients at risk for CKD in the long term. However, we were able to demonstrate that very early creatinine elevation between D3 and D5, which did not meet the criteria for AKI as they are not sensitive enough, was correlated with poorer kidney function at 6 months to 1 year [66,131]. Similarly, the need for temporary dialysis has been identified as a source of CKD [51] in the long run.…”
Section: Post-operative Risk Factorsmentioning
confidence: 78%
“…At the same time, the risk of developing renal dysfunction is correlated with the type of liver cirrhosis. In fact, viral cirrhosis related to hepatitis [14], non-alcoholic steatohepatitis (NASH), alcoholic cirrhosis and primary biliary cholangitis are recognized as risk factors for post-transplantation renal dysfunction [10,66,70,73,75,122,123,129,131]. Conversely, patients with cirrhosis complicated by hepatocellular carcinoma develop fewer renal dysfunctions after transplantation [42,95].…”
Section: Risk Factors Related To the Liver Impairmentmentioning
confidence: 99%
“…Most of the literature assessing variables associated with post-LT CKD examines clinical variables, rather than biomarkers. Only four studies were identified that assess the role of biomarkers in predicting post-transplant CKD [ 91 94 ]. Supplementary Table S4 summarizes baseline characteristics of the studies reviewed.…”
Section: Resultsmentioning
confidence: 99%
“…The developed protein (β2‐microglobulin, CD40)/clinical (hepatitis C virus infection) model has excellent performance in both the modeling group and the validation group, which helps to screen high‐risk population of CKD for early Intervention. However, another prospective study focused on urine protein failed to identify peptide‐based biomarkers related to CKD after transplantation [43].…”
Section: Resultsmentioning
confidence: 99%